Characteristics and meteorological mechanisms of transboundary air pollution in a persistent heavy PM2.5 pollution episode in Central-East China. (15th February 2020) - Shi, Chune; Nduka, Ifeanyichukwu C.; Yang, Yuanjian; Huang, Yong; Yao, Risheng; Zhang, Hao; He, Bingfang; Xie, Chengbo; Wang, Zhenzhu; Yim, Steve Hung Lam
Abstract: Previous research has shown the significant transboundary air pollution (TAP) in China. Despite its adverse environmental and human health impacts, the characteristics and mechanisms of TAP have yet to be fully understood. This study comprehensively analyzed intensive ground and upper levels measurements along with the atmospheric modeling approach to determine the driving meteorological conditions responsible for the formation and evolution of a persistent severe PM2.5 pollution episode in Central-East China (CEC, 112°E −118°E, 30°N −34°N) starting from 18:00 on Dec. 3 to 18:00 on Dec. 5, 2017, which had obvious characteristics of TAP and explosive increases in PM2.5 concentration. We assessed and quantified contributions of local and nonlocal emissions to PM2.5 in the region and different cities during the episode and determined the altitude level at which TAP occurred. Results show that PM2.5 concentration in most cities in CEC region experienced two major increases: the first increase was due to the change in wind direction from south to north, transporting pollutants from north China to CEC; the second increase was driven by several important meteorological factors, including warm/cold advection at different altitudes, large-scale subsidence, and radiative cooling, jointly resulting in a deep (reaching around 800 m) and strong elevated temperature inversion with a significant reduction in mixing layer thickness and thus causing a rapid increase in PM2.5 concentration in CEC region. On average, TAP accounted for 42% of total PM2.5 concentration in the region during the event, in which the TAP impact varied by cities, ranging from 26% to 70%. Our findings demonstrate the synergetic effect of TAP and large-scale subsidence, providing a critical reference for air pollution forecast and assessment in the eastern China. Highlights: The formation of the studied episode was due to southward movement of a high pressure system, large-scale subsidence, and inversion of boundary layer temperature. The slow-increase and rapid-increase phases in the episode were due to surface convergence and large-scale subsidence, respectively. Air pollutants in North China can be transported to CEC at the ground level and in free troposphere, while the surface transport was the dominant. Transboundary air pollution on average contributed 42% of the PM2.5 concentration in the Central-East region in the episode.